(untitled) (Ustozlar uchun, 2026)
This article investigates the development and current status of corpus linguistics in Uzbekistan, focusing on the construction, availability, and application of Uzbek-language corpora in linguistic research and language education. Using a mixed-methods approach that combines systematic review of existing corpora and published research with semi-structured interviews with ten Uzbek corpus linguists, the study identifies critical infrastructure gaps, methodological challenges, and institutional barriers that constrain the field. Results reveal that while several Uzbek corpora exist — including the Uzbek National Corpus and domain-specific sub-corpora — they remain significantly smaller and less annotated than comparable corpora for major world languages. Furthermore, corpus-based methods are underutilised in Uzbek linguistics pedagogy and applied language research. The article concludes with evidence-based recommendations for scaling corpus infrastructure, fostering interdisciplinary collaboration, and integrating corpus tools into university curricula. The findings contribute to the growing literature on corpus linguistics in under-resourced language contexts and provide a roadmap for Uzbek language technology development.